Physiological differences in response to di-n-butyl phthalate (DBP) exposure between low- and high-DBP accumulating cultivars of Chinese flowering cabbage (Brassica parachinensis L.). (January 2016) - Zhao, Hai-Ming; Du, Huan; Xiang, Lei; Li, Yan-Wen; Li, Hui; Cai, Quan-Ying; Mo, Ce-Hui; Cao, Gang; Wong, Ming-Hung
Abstract: To increase understanding on the mechanisms of cultivar difference in contaminant accumulation in crops, this study was designed to compare the physiological responses to di- n -butyl phthalate (DBP) exposure between low ( Lvbao70 ) and high ( Huaguan ) DBP cultivars of Chinese flowering cabbage ( Brassica parachinensis L.). Under high DBP exposure, significant differences in various physiological responses were observed between the two cultivars, which might account for the variation in DBP accumulation. Ultrastructure observation also showed different alterations or damages in the mesophyll cell structures between both cultivars, especially for the chloroplast disintegration, starch grain quantity, and plastoglobuli accumulation. Compared with Huaguan, Lvbao70 suffered greater decreases in biomass, chlorophyll content, carbon assimilation, gas exchange parameters, photosynthetic electron transport capacity, and antioxidase activities, which would have resulted in a great reduction of photosynthetic capacity. Although Lvbao70 enhanced energy dissipation and activities of some antioxidant enzymes, they did not provide sufficient protection against oxidative damage caused by DBP. The result suggested that the lower DBP tolerance of Lvbao70 might be associated with its poor physiological performances, which was responsible for its lower DBP accumulation to protect itself from toxicity. Additionally, Lvbao70 had a significantly lower transpiration rate and stomatal conductance than Huaguan, which might be the factors regulating DBP-accumulation variation. Graphical abstract: Highlights: Effects of physiology on DBP-accumulation variation were investigated in two cultivars. Low DBP-accumulating cultivar suffered more adverse effects under high DBP exposure. Photosynthesis of low DBP cultivar was more restrained than that of high DBP cultivar. Transpiration and stoma might play important roles in DBP-accumulation variation. Abstract : There were significant differences in physiological performances between the low and high DBP cultivars, which might account for their DBP-accumulation variation.